Nmap essentials : harness the power of Nmap, the most versatile network port scanner on the planet, to secure large scale networks - Shaw, David (Community experience distilled., 2015)
This book is for beginners who wish to start using Nmap, who have experience as a system administrator or of network engineering, and who wish to get started with Nmap.